ChemInform Abstract: Nucleophilic Substitution of the Hydroxyl Group in Stereogenic Alcohols with Chirality Transfer. Issue 25 (June 2016) - Bunrit, Anon; Dahlstrand, Christian; Srifa, Pemikar; Olsson, Sandra K.; Huang, Genping; Biswas, Srijit; Himo, Fahmi; Samec, Joseph S. M.
Abstract: An intramolecular substitution of the OH group in enantioenriched alcohols is achieved by acid/base bifunctional catalysis.